2020
DOI: 10.3390/ijms21228544
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate Gonadotropin-Releasing Hormone Receptor Signaling and Its Relevant Biological Actions

Abstract: Gonadotropin-releasing hormones (GnRHs) play pivotal roles in reproduction via the hypothalamus-pituitary-gonad axis (HPG axis) in vertebrates. GnRHs and their receptors (GnRHRs) are also conserved in invertebrates lacking the HPG axis, indicating that invertebrate GnRHs do not serve as “gonadotropin-releasing factors” but, rather, function as neuropeptides that directly regulate target tissues. All vertebrate and urochordate GnRHs comprise 10 amino acids, whereas amphioxus, echinoderm, and protostome GnRH-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…GnRH-like signaling in invertebrates regulates various aspects of reproduction and associated reproductive treats ( Sakai et al, 2020 ). Likewise, somatic activation of the gonadal longevity pathway is coupled with reproduction ( Shemesh et al, 2017b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GnRH-like signaling in invertebrates regulates various aspects of reproduction and associated reproductive treats ( Sakai et al, 2020 ). Likewise, somatic activation of the gonadal longevity pathway is coupled with reproduction ( Shemesh et al, 2017b ).…”
Section: Resultsmentioning
confidence: 99%
“…The gonadotropin-releasing hormone (GnRH) superfamily acts at the interplay between development and reproduction. This superfamily integrates internal and environmental stimuli to regulate sexual maturation and reproductive functions in vertebrates and invertebrates ( Zandawala et al, 2018 ; Sakai et al, 2020 ). This G protein-coupled receptor (GPCR) superfamily is subdivided into two main subfamilies based on neuropeptides sequence conservation.…”
Section: Introductionmentioning
confidence: 99%
“…At the time, this further strengthened the assumption that invertebrate and vertebrate endocrinology are similar including the presence of a homologous system for the vertebrate hypothalamic-pituitary-gonadal axis. Since then we have found that these peptides are multifunctional and do not have a specific reproductive function as seen in vertebrates (38)(39)(40)(41)(42)(43). As a result, more studies have investigated these peptides and/or their assumed related molecules [e.g., follicle-stimulating hormone (FSH)] in mollusks with antibodies raised against vertebrate molecules (44-47); most likely resulted in non-specific results and so inappropriate conclusions.…”
Section: Nominative Determinismmentioning
confidence: 99%
“…Gonadotropin releasing hormone receptor (GnRHR) is a G protein coupled receptor. Previous studies have indicated that GnRH combines with GnRHR on the target cell membrane, and activates the intracellular signaling pathway to complete its biological function [ 16 , 17 ]. Follicle stimulating hormone receptor (FSHR) is an important member of HPG axis, which plays a vital role in granulosa cell (GC) proliferation, apoptosis and differentiation, as well as follicle development and ovulation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%